2019
DOI: 10.3389/fmicb.2018.02898
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Persistence of High-Risk Clones Among MDR and XDR A. baumannii at a Brazilian Teaching Hospital

Abstract: Dissemination of carbapenem-resistant Acinetobacter baumannii is currently one of the priority themes discussed around the world, including in Brazil, where this pathogen is considered endemic. A total of 107 carbapenem-resistant A. baumannii (CRAB) isolates were collected from patients with bacteraemia attended at a teaching hospital in Brazil from 2008 to 2014. From these samples, 104 (97.2%) carried blaOXA−23−like, all of them associated with ISAba1 The blaOXA−231 (1.9%) and blaOXA−72 (0.9%) genes were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 54 publications
0
8
1
2
Order By: Relevance
“…The importance of A. baumannii clinical isolates belonging to IC4 and IC5 in South America has been previously demonstrated (Cieslinski et al, 2013;Stietz et al, 2013;Rodríguez et al, 2016;Opazo-Capurro et al, 2019;Müller et al, 2019). The higher frequency of those clones was also observed in different regions in Brazil and has been associated with an XDR phenotype (Royer et al, 2018;Pagano et al, 2019;Tavares et al, 2019). Interestingly, despite their wide distribution through time and space, the IC4 and IC5 clinical isolates included in this study remained highly genetically related, as determined using both PFGE and cgMLST.…”
Section: Discussionmentioning
confidence: 51%
“…The importance of A. baumannii clinical isolates belonging to IC4 and IC5 in South America has been previously demonstrated (Cieslinski et al, 2013;Stietz et al, 2013;Rodríguez et al, 2016;Opazo-Capurro et al, 2019;Müller et al, 2019). The higher frequency of those clones was also observed in different regions in Brazil and has been associated with an XDR phenotype (Royer et al, 2018;Pagano et al, 2019;Tavares et al, 2019). Interestingly, despite their wide distribution through time and space, the IC4 and IC5 clinical isolates included in this study remained highly genetically related, as determined using both PFGE and cgMLST.…”
Section: Discussionmentioning
confidence: 51%
“…Despite the reports that the A. baumannii strains isolated in Brazilian hospitals are MDR, the susceptibility of those isolates to the last choice drugs, such as polymyxins, still prevails ( Leite et al, 2016 ; Sader et al, 2016 ; Castilho et al, 2017 ; Vasconcellos et al, 2017 ). For instance, in a Brazilian teaching hospital, Tavares et al (2019) found MDR and XDR A. baumannii clones were emerging, including CC1 strains, as the second most prevalent; on the other hand, although MDR or XDR, none of the strains was resistant to polymyxin B ( Tavares et al, 2019 ). Nevertheless, the high incidence of polymyxin resistance found in the A. baumannii isolates evaluated in this study (37.5%) highlights the need for constant surveillance of antimicrobials resistance, particularly to the drugs used as last resources, in all the species isolated at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The ST1 PAS /ST109 OXF (Clone C; n = 9), ST79 PAS /ST758 OXF (Clone A; n = 12) and ST78 PAS / ST944 OXF (Clone B; n = 6), corresponded to the highrisk pandemic International Clone I (IC-1), International Clone V (IC-5) and International Clone VI (IC-6), respectively (Table). (20,26,27,28,29) Previous studies had already reported the dissemination and the high prevalence of multidrug resistant A. baumannii from CC1 (ST1/IC-1), CC15 (ST180) and CC79 (ST79/IC-5) in Brazil. (9,10,11) Here, it was demonstrated that CC1 and CC79 are also prevalent in a clinical setting from the Amazon Region (Table).…”
Section: Resultsmentioning
confidence: 99%